Key players in national SDG accountability: The role of parliaments - Anita Breuer; Julia Leininger; Kirsten Brosbøl; Léna Belly-Le Guilloux; Saionara König-Reis; Bora Sefa (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
Achieving the Sustainable Development Goals (SDGs) of the 2030 Agenda will require strong accountable institutions. Since no global compliance mechanisms are in place, member states need to establish or use their own institutions to be held accountable for SDG implementation. In July 2021, governments, civil society and the private sector will gather at the annual UN High-level Political Forum on Sustainable Development (HLPF) to take stock of progress on the 17 SDGs. The event provides an opportunity to assess progress made in the establishment of national-level accountability frameworks for the SDGs. As representatives of the people, parliaments should play a key role in localising the 2030 Agenda and holding governments accountable to their commitments. Over recent years, some progress has been made in enabling parliaments around the world to fulfil their accountability functions. Most notably, almost half of the countries that presented Voluntary National Reviews (VNRs) between 2016 and 2019 reported that capacity-building events took place to inform members of parliament about the SDGs, and parliaments are being increasingly consulted by governments in the process of preparing the VNRs. However, in addition to a lack of awareness about the 2030 Agenda, several factors constrain parliaments' SDG accountability function. In many countries, parliamentarians lack access to the data needed to assess governments' SDG performance, and only few governments have committed to regularly report on SDG progress beyond the VNRs. Furthermore, only in a quarter of countries has responsibility for the SDGs been clearly assigned within the structures of parliament itself. In addition, thus far, parliaments have only been weakly involved in processes of localising the SDGs through the adoption of national SDG implementation strategies and the development of national priority goals and indicators. In general, legislatures' ability to hold governments accountable has decreased amidst recent autocratisation trends. Good practices to overcome these obstacles include the use of digital tools to increase the transparency of governments' fiscal behaviour vis-à-vis parliament and the creation of discursive formats to foster parliament-government dialogues about sustainability transformation. Peer learning will play an important role in disseminating information about such empowering practices among parliamentarians worldwide. More importantly, however, national governments need to recognise parliaments as critical actors in the SDG process. Amidst current autocratisation trends worldwide, peer pressure by the international community, pressure by independent media and NGOs, and the support of UN agencies will be necessary to strengthen the role of parliaments in promoting SDG accountability. Parliaments themselves should seek to establish dedicated SDG committees with formal powers to undertake in-depth examinations of government action as well as legislation. This will also contribute to the continuity of parliamentary SDG activities beyond electoral cycles.
Keywords: 330